Use of Advanced Technology in Artifact Preservation by Archivist in Awka Museum, Anambra State - Ugochi Iruoma Egwuonwu; Vivian Ukachi Nwaobasi; Ugochi Gladys Okeke; Josiah Ibezim Ekwebelem (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The study surveyed the Use of advanced technology in artifact preservation by archivist in Awka Museum,Anambra State. two research questions guided the research. Descriptive survey research design was used for the study. The population of the study was made up of 8 archivist in Awka Museum,Anambra State. Census sampling was used. The instruments for data collection were the checklist and questionnaire. Data was analyzed using mean scores. The findings of the study revealed that the majority of the advanced technology such as blockchain, augmented reality tools, IoT-based sensor networks, and UV light filtering systems were not available for artifact preservation in Awka museum. The majority of the advanced technology such as augmented reality, 3D digitization, RFID systems, and IoT-based sensors were not used by archivist in artifact preservation in Awka museum. The study recommended the establishment of strategic partnerships with technology providers to secure funding and donations aimed specifically at procuring advanced preservation technologies such as blockchain systems, and IoT sensor networks.